Towards Model Driven Architecture in Academic Quality Assurance Information System Development - Mokhtar, Rashidah; Abdul Rahman, Azizah; Othman, Siti Hajar (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
In this research, we present the use of a Model Driven Architecture (MDA) in academic quality assurance (AQA) domain. To provide a detailed analysis of MDA, we show how the paradigm of MDA can be configured to implement the AQA application software based on information system (IS) platform. An extensive analysis of AQA models is constructed to extract the concepts and simultaneously created a metamodel that can be reused for similar projects. The sixstepwise of Othman and Beydoun metamodelling development is used to develop the metamodel. Then, the demonstration of usefulness of the metamodel is shown through instantiation and conformance process. The future development of AQA Knowledge Repository (AQA-KR) will ensures that users can use the stored knowledge to develop AQA solutions as AQA contexts vary